POLA PENGAMBILAN KEPUTUSAN MENGENAI PARTISIPASI DALAM PROGRAM KELUARGA BERENCANA PADA KELUARGA MUDA DI KOTA MALANG - Anggaunita Kiranantika (Jurnal Sejarah dan Budaya, 2013)
Abstract.This study focused on the young family decision making which fully participated on “Keluarga Berencana (Family Planning)” program in Malang city. Research used quantitative methods whereas tables and numbers getting on priority. Research type is descriptive, then populations were spouse on 0-10 years marriage. Furthermore, systematic random sampling is used for 100 respondents. Research finding that majority women roles are not only for domestic but also as principal decision maker on their family. In addition to this research, women has created her own rights inside the family without any intervention from their spouse.